INVASIVE AUTOLOGOUS PLASMIN TREATMENT FOR DIFFUSE DIABETIC MACULAR EDEMA: A PROMISING APPROACH - Dr. Pulgurthi Ramgopal (Journal of Population Therapeutics and Clinical Pharmacology, 2013)
In one study, IAP injections and triamcinolone acetonide injections are being compared for Diabetic macular edema in diffuse form. 66.4% of the population is older than 64 and 14.4% of the population has diabetes for 14 years or more were measured for the 100 diabetic patients in this study. There were 36 males and 64 females. Two groups of patients were randomly assigned to receive 4 mg TA or 0.2 mL Autologous plasmin freshly prepared after undergoing a full ophthalmologic examination and a full ophthalmologic examination. CMT, BCVA, and IOP were measured at 1, 3, and 6 months to determine the outcome of the study. There was no significant difference between the two groups in the reduction of CMT thickness after TA and plasmin treatment, as both decreased it significantly when compared to baseline thickness. At 6 months after injection, CMT peaked again but remained lower than baseline after 1 month after injection. Plasmin showed less improvement than 1-month measurement and each other. As compared to the BCVA in the IAP group at baseline and at 1 and 3 months, the BCVA in the TA group considerably declined after 6 months. One month after injection versus one month after injection, both groups had lower IOP at 3 and 6 months, although the TA group had a significantly higher IOP, whereas the IAP group did not have a significantly lower IOP. A significant difference was noted between IAP and TA groups in terms of Three- and six-month estimates of IOP. In summary, IAP injections decreased CMT and improved BCVA more effectively than intravitreal injections of TA, and this was safer and longer lasting than intravitreal injections of TA.